Ken Dark and Jan Kostenec, Hagia Sophia in Context - ΕΥΘΥΜΙΑΔΗΣ (Stefanos EFTHYMIADIS), Στέφανος (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2021)
Ken Dark and Jan Kostenec, Hagia Sophia in Context. An Archaeological Re-examination of the Cathedral of Byzantine Constantinople, Oxbow Books, Oxford ‒ Havertown, PA 2019 ‒ X & 141 σελ. ISBN: 978-1- 78925-030-5, Digital Edition: ISBN 978-1-78925-031-2 (epub).